Tìm x biết
(X-2)×(x-3)<0
X×x-2x>0
X×x-5x <0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\((x-6)(3x-9)>0\)
TH1:
\(\orbr{\begin{cases}x-6< 0\\3x-9< 0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x< 6\\x< 3\end{cases}}\)\(\Rightarrow x< 3\)
TH2:
\(\orbr{\begin{cases}x-6>0\\3x-9>0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x>6\\x>3\end{cases}}\)\(\Rightarrow x>6\)
Vậy \(x< 3\) hoặc \(x>6\)thì \((x-6)(3x-9)>0\)
Học tốt!
20.
\((2x-1)(6-x)>0\)
TH1:
\(\orbr{\begin{cases}2x-1>0\\6-x>0\end{cases}\Rightarrow\orbr{\begin{cases}x< \frac{1}{2}\\x< 6\end{cases}}\Rightarrow x< 6}\)
TH2
\(\orbr{\begin{cases}2x-1< 0\\6-x< 0\end{cases}\Rightarrow\orbr{\begin{cases}x>\frac{1}{2}\\x>6\end{cases}}\Rightarrow x>\frac{1}{2}}\)
Vậy \(x< 6\)hoặc \(x>\frac{1}{2}\)thì \((2x-1)(6-x)>0\)
a: (x-2)(x+3/4)>0
=>x-2>0 hoặc x+3/4<0
=>x>2 hoặc x<-3/4
b: (2x-5)(1-3x)>0
=>(2x-5)(3x-1)<0
=>3x-1>0 và 2x-5<0
=>1/3<x<5/2
c: (3-2x)(x+1)<0
=>(2x-3)(x+1)>0
=>2x-3>0 hoặc x+1<0
=>x>3/2 hoặc x<-1
d: (5x+11)(7-x)<0
=>(5x+11)(x-7)>0
=>x>7 hoặc x<-11/5
a, \(\left(2-x\right)\left(x+3\right)>0\Leftrightarrow\left(x-2\right)\left(x+3\right)< 0\)
Vì \(x+3>x-2\)
nên \(\hept{\begin{cases}x+3>0\\x-2< 0\end{cases}}\Leftrightarrow\hept{\begin{cases}x>-3\\x< 2\end{cases}\Leftrightarrow-3< x< 2}\)
c, \(\left(5-2x\right)\left(x+4\right)>0\)
TH1 : \(\hept{\begin{cases}5-2x>0\\x+4>0\end{cases}}\Leftrightarrow\hept{\begin{cases}x< \frac{5}{2}\\x>-4\end{cases}}\Leftrightarrow-4< x< \frac{5}{2}\)
TH2 : \(\hept{\begin{cases}5-2x< 0\\x+4< 0\end{cases}}\Leftrightarrow\hept{\begin{cases}x>\frac{5}{2}\\x< -4\end{cases}}\)( vô lí )
bạn làm tương tự nhé
\(\left(x-2\right)\left(x-3\right)< 0\\ \Rightarrow\left(x-2\right)\text{ và }\left(x-3\right)\text{khác dấu}\)
\(\left\{{}\begin{matrix}x-2>0\\x-3< 0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x>2\\x< 3\end{matrix}\right.\Rightarrow2< x< 3\\ \left\{{}\begin{matrix}x-2< 0\\x-3>0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x< 2\\x>3\end{matrix}\right.\left(loai\right)\)
Vậy ...
\(x\cdot x-2x>0\Rightarrow x\left(x-2\right)>0\Rightarrow x\text{ và }x-2\text{ cùng dấu}2\)
\(\left\{{}\begin{matrix}x>0\\x-2>0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x>0\\x>2\end{matrix}\right.\Rightarrow x>2\\ \left\{{}\begin{matrix}x< 0\\x-2< 0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x< 0\\x< 2\end{matrix}\right.\Rightarrow x< 2\)
Vậy ...
\(x\cdot x-5x< 0\Rightarrow x\left(x-5\right)< 0\Rightarrow x\text{ và }x-5\text{ khác dấu}\)
\(\left\{{}\begin{matrix}x>0\\x-5< 0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x>0\\x< 5\end{matrix}\right.\Rightarrow0< x< 5\\ \left\{{}\begin{matrix}x< 0\\x-5>0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x< 0\\x>5\end{matrix}\right.\left(loai\right)\)
Vậy ...